2001
DOI: 10.1002/1521-3773(20010417)40:8<1449::aid-anie1449>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Acetylenes Rearranging on Ruthenium-Porphyrinogen and Leading to Vinylidene and Carbene Functionalities

Abstract: Through a proton‐transfer reaction a porphyrinogen assists the transformation of terminal acetylenes into Ru–vinylidenes, which are the entry point to a variety of Ru–carbenes and Ru–cumulenes. The scheme (in which the porphyrinogen is stylized) shows the reversible interconversion of an acetylide into a divinylidene unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…First investigated by Floriani et al in 2001, 14,15 the ruthenium(II) platform [1] 2− has been reported to support a variety of ruthenium−main group multiple bonds. 14−16 Our studies began by interrogating the reaction between Na 2 (DME) 6 [1] and t BuPA by NMR spectroscopy in tetrahydrofuran (THF)-d 8 .…”
supporting
confidence: 82%
See 2 more Smart Citations
“…First investigated by Floriani et al in 2001, 14,15 the ruthenium(II) platform [1] 2− has been reported to support a variety of ruthenium−main group multiple bonds. 14−16 Our studies began by interrogating the reaction between Na 2 (DME) 6 [1] and t BuPA by NMR spectroscopy in tetrahydrofuran (THF)-d 8 .…”
supporting
confidence: 82%
“…Our recent work on phosphinidene transfer from dibenzo-7-phosphanorbornadiene RP A compounds ( A = C 14 H 10 or anthracene) has positioned us well to explore [RP] unit delivery to a metal center. We now report facile phosphinidene transfer from a series of RP A compounds to the ruthenium­(II) calix[4]­pyrrole (“porphyrinogen”) complex Na 2 (DME) 6 [ 1 ] (Figure , DME = 1,2-dimethoxyethane). , The electronic structure of the resulting RuP bond is strongly influenced by the substituent, an effect that we have characterized through 31 P MAS SSNMR spectroscopy. The chemical shift tensor is shown to be a direct experimental handle on the σ RuP /π RuP * energy gap and its orientation on the nature of the phosphorus–substituent σ PR bond.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AM in homogeneous nitrogen reduction and ammonia synthesis (A) Catalytic reduction of N 2 in the presence of [(TPB)Fe(N 2 )][Na(12-crown-4) 2 ] using excess KC 8 and HBAr F 4 $2Et 2 O in diethyl ether (Et 2 O) at -78 C. Adapted with permission from Peters et al48 Copyright 2013 Springer Nature. (B) The N-N distances of selected TM-N 2 complexes with end-on or side-on interactions to AM cations, and several N 2 -derived multinuclear TM-N complexes with nitride-AM cation interactions 44,45,13,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. Noted that the N-N bond in multinuclear TM-N complexes is dissociated.…”
mentioning
confidence: 99%
“…This reaction was shown to be reversible, and the bis-vinylidene complex can be reduced back to the respective acetylide complex with sodium naphthalenide. 57 Similar reactivity has been observed for the iron complex [Fe(Cp*)(dppe)-(CRCH)], yielding the bis-vinylidene complex {[Fe(Cp*)(dppe)] 2 (m 2 -CCHCHC)} 2þ upon one-electron oxidation. 58 with Cu þ .…”
Section: Open-shell Reactivity Of Alkenyl (Acetylide) Ligandsmentioning
confidence: 99%